2007
DOI: 10.2478/s11658-006-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic heart failure enhances endogenous myocardial apelin and APJ receptor expression

Abstract: Abbreviations used: CHO -Chinese hamster ovary; DTT -dithiothreitol; EDTAethylenediaminotetraacetic acid; EIA -enzyme immunoassay; LAD -left anterior descending; SDS -sodium dodecyl sulphate Abstract: Apelin interacts with the APJ receptor to enhance inotropy. In heart failure, apelin-APJ coupling may provide a means of enhancing myocardial function. The alterations in apelin and APJ receptor concentrations with ischemic cardiomyopathy are poorly understood. We investigated the compensatory changes in endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 23 publications
7
69
4
2
Order By: Relevance
“…However, APJ mRNA is decreased in the weakened and enlarged heart of humans with idiopathic dilated cardiomyopathy (Foldes et al 2003). Apelin may have a cardioprotective role in hypoxia and ischaemia, where the cardiac levels of apelin and APJ respectively are increased (Atluri et al 2007, Ronkainen et al 2007, Zeng et al 2009). Apelin may also play a protective a role in ischaemia/reperfusion injury , Zeng et al 2009), although the method of signalling appears to be independent of the characteristic myocardial kinase cascade, termed the reperfusion injury salvage kinase pathway (Kleinz & Baxter 2008).…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%
“…However, APJ mRNA is decreased in the weakened and enlarged heart of humans with idiopathic dilated cardiomyopathy (Foldes et al 2003). Apelin may have a cardioprotective role in hypoxia and ischaemia, where the cardiac levels of apelin and APJ respectively are increased (Atluri et al 2007, Ronkainen et al 2007, Zeng et al 2009). Apelin may also play a protective a role in ischaemia/reperfusion injury , Zeng et al 2009), although the method of signalling appears to be independent of the characteristic myocardial kinase cascade, termed the reperfusion injury salvage kinase pathway (Kleinz & Baxter 2008).…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%
“…Hypoxia up-regulates apelin synthesis in cardiovascular tissues (Ronkainen et al 2007) as does ischaemic cardiomyopathy in rats (Atluri et al 2007). This may occur as a compensatory mechanism with the failing heart attempting to maintain normal function by increasing ventricular apelin.…”
Section: Apelinmentioning
confidence: 99%
“…This cardiac apelin is restored by treatment with angiotensin type 1 blocker (Iwanaga et al 2006). However, myocardial expression of apelin is increased in ischaemic heart failure (Atluri et al 2007). So myocardial expression of apelin may be decreased or increased but plasma levels of apelin are decreased in patients with chronic heart failure (Foldes et al 2003, Chong et al 2006.…”
Section: Apelinmentioning
confidence: 99%
“…Apelin is expressed primarily in the endothelium and acts both locally and via endocrine signaling to activate APJ, which is expressed on myocardial cells, endothelial cells, and some SMCs (3)(4)(5)(6). In isolated rat cardiomyocytes and intact hearts as well as with in vivo rat and mouse models, apelin has been shown to have a positive effect on contractility (7)(8)(9)(10). Experiments employing myocardial injury models have suggested that apelin also has a positive inotropic effect on failing myocardium (8,11).…”
Section: Introductionmentioning
confidence: 99%